2020
DOI: 10.1093/ofid/ofaa439.851
|View full text |Cite
|
Sign up to set email alerts
|

658. Effect of HIV Status on Tuberculosis Load as Detected by Xpert MTB/RIF in Sputum vs. Saliva Samples

Abstract: Background Tuberculosis (TB) is the most common co-infection among people living with HIV, but HIV positivity is associated with a lower Mycobacterium tuberculosis (MTB) bacillary load in sputum, making TB often difficult to diagnose with current diagnostic solutions. GeneXpert MTB/RIF (Cepheid, USA), a rapid, molecular diagnostic assay, has transformed the TB diagnostic landscape and can be used to diagnose TB and limited drug resistance in HIV patients from direct clinical samples in &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Xpert has been shown to be a reliable measure of bacterial burden through multiple studies (9,13). Additionally, a retrospective study compared CT values collected from sputum and saliva from both people living with and without HIV (14). Burger et al concluded that patients living with HIV had significantly lower bacterial load than individuals without HIV, and sputum is the optimal sample type for Xpert analysis (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xpert has been shown to be a reliable measure of bacterial burden through multiple studies (9,13). Additionally, a retrospective study compared CT values collected from sputum and saliva from both people living with and without HIV (14). Burger et al concluded that patients living with HIV had significantly lower bacterial load than individuals without HIV, and sputum is the optimal sample type for Xpert analysis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a retrospective study compared CT values collected from sputum and saliva from both people living with and without HIV (14). Burger et al concluded that patients living with HIV had significantly lower bacterial load than individuals without HIV, and sputum is the optimal sample type for Xpert analysis (14). Combined, these studies support the observation that HIV changes the presentation of TB, with less inflammation and cavitation leading to lower TB bacterial load (9,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Also, HIV and TB coinfected patients have weaker immune systems and lower bacterial load in sputum, making the detection of TB harder through conventional methods. 14,15 The prevalence of TB in newly diagnosed HIV patients was 17.8% in a study from Gujarat 16 and 29.6% in a survey from Telangana. 17 Pulmonary TB can occur at all stages of HIV infection.…”
Section: Pulmonary Tuberculosis and Human Immunodeficiency Virusmentioning
confidence: 97%
“…These may manifest as pseudoaneurysms (►Fig. 14), hypertrophied bronchial arteries (►Fig. 15), systemic collaterals, chronic empyema, fibrothorax, bronchopleural fistula, pneumothorax, mediastinal fibrosis, pericarditis, and spondylodiskitis.…”
Section: Tuberculosis Complications and Other Coinfectionsmentioning
confidence: 99%